Strategic site selection of microalgae industry in the Philippines using analytic hierarchy process - Ubando, Aristotle T. (Animo Repository, 2015)
Microalgae are microorganisms which converts sunlight and carbon dioxide to useful biomass. It consists of high-valued contents such as protein, carbohydrates, lipids and pigments which can yield various industrial products: nutraceuticals, animal feeds, and biofuels. Since the Philippines was found to have an abundance of microalgae species due to its tropical climate and archipelagic nature, a strategic multicriteria site selection decision structure must first be established for potential deployment of cultivation and processing locations involving multiple industries. Analytic hierarchy process (AHP) was utilized to develop the strategic decision structure of the study. A survey from a panel of stakeholders was conducted to identify the prioritization between criteria via pairwise comparison method. The results revealed the preferred regions of the Philippines suitable for an anticipatory microalgal industry. The developed decision structure aims to aid policy makers and stakeholders for the deployment of the emerging industry. Future work involves the consideration of uncertainty of judgment from the panel of stakeholders. Copyright © 2015, AIDIC Servizi S.r.l.,.